Prevalence of the colonization by Streptococcus agalactiae in pregnant women from a public health system in Santo Ângelo - RS - Franciane Rios Senger; Izabel Almeida Alves; Débora da Cruz Payão Pellegrini; Daiane Cristina Prestes; Edú Fraga de Souza; Ezequiel Dalla Corte (Universidade de Santa Cruz do Sul, 2016)
ABSTRACT: Background and Objectives: Streptococcus agalactiae (GBS) is part of the female genital tract microbiota, however, its clinical significance is related to infections in newborns and can cause severe cases of pneumonia, septicemia and meningitis. Thus, the aim of this study is to determine the prevalence of colonization by S. agalactiae in pregnant women and analyze the sensitivity profile of the isolated front of antimicrobials. Methods: Vaginal and anorectal samples of pregnant women over 30 weeks of gestation were collected from February to June 2013. The samples were stored in Stuart transport medium and then inoculated in Todd-Hewitt broth added gentamicin and acid nalidixic with subsequent subculture on blood agar plates. For identification were performed Gram test, catalase, CAMP and latex agglutination. Furthermore, the antimicrobial susceptibility tests and the test for the detection of resistance induced clindamycin in the samples resistant to erythromycin were conducted. They are also assessed, through interviews, demographic, socioeconomic and clinical and obstetric data. Results: It was observed colonization in 22.5% (18/80) of the pregnant women. The strains were sensitive to most of the antibiotics tested except erythromycin, showing a resistance of 22.2% (4/18) isolates. However, none of the samples erythromycin resistant had induced resistance to clindamycin. Conclusion: The high maternal colonization by S. agalactiae found emphasize the importance of isolation of this bacterium in late pregnancy, preventing the occurrence of neonatal infection. KEYWORDS: Streptococcus agalactiae. Pregnancy. Prevalence.